Preparation of Ag-Coated SiO2@TiO2 Core-Shell Nanocomposites and Their Photocatalytic Applications towards Phenol and Methylene Blue Degradation. (15th October 2019) - Fu, Ning; Ren, Xue-chang; Wan, Jian-xin
Abstract : Ag-coated SiO2 @TiO2 (Ag-SiO2 @TiO2 ) core-shell nanocomposites were synthesized by a two-step method, which combined hydrothermal process and photodeposition. The morphology, structure, composition, and optical properties of the Ag-coated SiO2 @TiO2 nanocomposites were extensively characterized by field-emission scanning microscopy (FE-SEM), transmission electron microscopy (TEM), energy-dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and Fourier-transform infrared spectra (FT-IR spectra). The anatase TiO2 nanoparticles (5-10 nm) with high surface area were loaded on SiO2 spheres (200-300 nm) in the form of SiO2 @TiO2 core-shell nanoparticle with a porous shell of controlled thickness (10–30 nm). Ag nanoparticles of different mass concentrations were photodeposited on SiO2 @TiO2 core-shell structure with particle sizes of about 10-20 nm. The results showed that Ag nanoparticles increased the photocatalytic activity of SiO2 @TiO2 core-shell nanoparticle improved the degradation of phenol and methylene blue under UV irradiation. The experimental results showed that Ag nanoparticles with mass concentrations of 6% had the highest photocatalytic activity on SiO2 @TiO2 core-shell nanoparticles.